MANGANESE ABUNDANCES IN THE ATMOSPHERE OF CLUMP GIANTS - Gorbaneva, T. I. (Одеські астрономічні публікації, 2013)
The manganese abundances was determined in the atmospheres of clump giants stars whose election was made earlier based on their chemical composition and evolutionary tracks. The spectra of the studied stars were obtained using the facilities of the 1.93m telescope of the Haute-Provence Observatoire (France) equipped with the échelle spectrograph ELODIE (R = 42000, S/N = 100–300). The Mn abundances was determined under the LTE approximation by the synthetic spectrum approach with a detailed consideration of the superfine structure. The behaviour of manganese abundances with metallicity [Fe/H] was considered.